The theory of the development of an electromagnetic engine for automotive use - Rahman, Mohammed Ataur; Rahman, Mizanur; Karim, Hafizzul (Symbiosis Group LLC., 2017)
The need to reduce the emission emitted from IC engine powered vehicle is paramount, as Malaysia has pledged to reduce 40% of CO2 intensity by 2020 from 2005 level by 25% improvement in average fuel consumption. The introduction of Electromagnetic Engine (EE) is one of the initiatives, however the electromagnetic engine could face several weaknesses amongst which are: limited driving range, thermal control, charging infrastructure, and overall limited efficiency. This study presents an electromagnetic propulsion system for automotive use that has a total different operating sequence compared to IC engines. It works by the principle of magnetic attraction and repulsion between electromagnet and a permanent magnet. The power supply interruption made by means of the reed switch to move down the piston. Thus, the back-and-forth movement of the piston occurs without failure. The experiment has been conducted on the determination of the electromagnetic engine performance by varying the applied loads on the crankshaft. The efficiency has been found of the model EME in the range of 12-20%. However, it could be achieved about 40-45% by proper sealing the magnetic flux of the electromagnet and alignment, exact fitting the piston and cylinder and prevent the magnetic flux leaking and heat generation, and the development